2021
DOI: 10.3390/data6080081
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of Gravity-Induced Landforms and Sinkholes of the Northeast Coast of Malta (Central Mediterranean Sea)

Abstract: This study investigates gravity-induced landforms that populate the North-Eastern coast of Malta. Attention is focused on tens of persistent joints and thousands of boulders associated with deep-seated gravitational slope deformations (DGSDs), such as lateral spreads and block slides. Lateral spreads produce deep and long joints, which partially isolate limestone boulders along the edge of wide plateaus. These lateral spreads evolve into large block slides that detach thousands of limestone boulders from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Mateos et al [17] reported an average velocity of the same order of magnitude (5.2 mm/yr) in a large lateral spreading along the North coast of Majorca (Spain). Extensive lateral spreading and block sliding processes in a geological setting comparable to the Chgega landslide have been under investigation since 2006 in the North part of Malta [8,9,[64][65][66]. In this area, long-term differential GNSS monitoring outputs carried out gave displacement rates between 0.8 and 2.4 cm/yr in a limestone plateau affected by lateral spreads and downslope blocks moved from block slides [64].…”
Section: Motion Detected In Chgega and In Other Similar Landslidementioning
confidence: 99%
See 1 more Smart Citation
“…Mateos et al [17] reported an average velocity of the same order of magnitude (5.2 mm/yr) in a large lateral spreading along the North coast of Majorca (Spain). Extensive lateral spreading and block sliding processes in a geological setting comparable to the Chgega landslide have been under investigation since 2006 in the North part of Malta [8,9,[64][65][66]. In this area, long-term differential GNSS monitoring outputs carried out gave displacement rates between 0.8 and 2.4 cm/yr in a limestone plateau affected by lateral spreads and downslope blocks moved from block slides [64].…”
Section: Motion Detected In Chgega and In Other Similar Landslidementioning
confidence: 99%
“…This phenomenon creates an unusual rugged relief formed by lateral spreading and block sliding processes [7]. Other places where large lateral spreading and block-type slope movements of carbonate rock formations overlie clayey-marly rocks can be found include Malta [8,9], Sicily [10], and Roccalbegna-Mt.Labbro (Italy) [11]. The combination of morphological features produced by this type of movement can create landmark sceneries, even regional symbols for the local population (e.g., the Trotternish landslides on the Isle of Skye, Scotland [12]) and some are nominated as geosites (e.g., crevice caves generated by mass movements in the UK [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Calleja 2010) or pluvial storm flooding (Malta Resources Authority 2013) or is focused on the evidence for extreme events in the past: their causes; processes of initiation and their impacts. This has included work on past tsunamis (Biolchi et al 2016;Causon Deguara and Gauci 2017;Mottershead et al 2018) and geomorphological phenomena including landslides, rock fall, sea-arch collapses and dolines (Mantovani et al 2013;Prampolini et al 2018;Satariano and Gauci 2019;Devoto et al 2021). Recent research has not only criticised the catalogue of, and policies associated with, pluvial storm flooding, but has also highlighted that Malta is exposed to a much wider range of environmental extremes than has been commonly supposed (Jones 2018;Main et al 2018;Main 2019) In this paper and accompanying supplementary material (Table S1) we publish Malta's first multi-hazard historical catalogue in which geophysical, geomorphological and meteorological extremes are recorded, identified and in some cases inferred, from the Miocene epoch (c. 23-c. 25 Ma) to 2019 CE.…”
Section: Maltamentioning
confidence: 99%
“…rock-fall, lateral spreads, block-slides) are common along extensive areas of the north Malta and east Gozo coasts and are directly associated with the geological setting, generally, and the northeast-southwest trending faults more particularly (e.g. Fig.3;Devoto et al 2012;Prampolini et al 2018;Soldati et al 2019;Devoto et al 2021). Although there are instances of rock-falls and landslips inland within our catalogue, these are largely the consequence of erosion and collapse of fissures within the Globigerina Limestone formation and historic bastion defences with some successful mitigation measures being installed to protect heavily visited historic sites such as…”
mentioning
confidence: 99%
“…Rocky coasts represent zones with high economic, social, cultural, and touristic value; consequently, many geomorphological studies have been completed along both hard and soft rocky coasts, which generally focused on the factors controlling erosional processes [3]. Moreover, other studies focused on the active morphodynamics along coastal reliefs, emphasizing the role of mass movements along sea cliffs on the present morphoevolution of the coastlines, also considering the associated geomorphologic hazards [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%